Sustainable learning for refugee children in South African primary schools: A theoretical approach - Rasheedah O. Adams-Ojugbele (AOSIS, 2021)
Background: The advent of democracy in South Africa brought about many changes in the education system. Policies and frameworks that guide the embracement of refugee children were formulated and later implemented. However, there are ongoing challenges experienced by this group and the incidents of poor access and quality of provision experienced by a larger population of refugee children, calls for urgent redress.